Spomini na medčasje - Podjed, Dan (Etnolog. Nova vrsta (Ljubljana), 2023)
The article focuses on the phenomenon of the meantime, i.e. the time in-between, in which the ordinary temporality is transformed into something new, carrying a different quality. The author first makes an overview of how anthropologists worked towards an understanding of the meantime during the COVID-19 pandemic, and then describes the remembering and changing of an individual stuck in prolonged isolation due to illness. Through their experience, he seeks to explain what kind of human being is made in the meantime and how the analysis of an individual’s specific situation can contribute to an understanding of global and local developments and perceptions of time in The article focuses on the phenomenon of the meantime, i.e. the time in-between, in which the ordinary temporality is transformed into something new, carrying a different quality. The author first makes an overview of how anthropologists worked towards an understanding of the meantime during the COVID-19 pandemic, and then describes the remembering and changing of an individual stuck in prolonged isolation due to illness. Through their experience, he seeks to explain what kind of human being is made in the meantime and how the analysis of an individual’s specific situation can contribute to an understanding of global and local developments and perceptions of time in crises.
Keywords: anthropological research; Antropološke raziskave; crises; Družbena izključenost; Krize; liminality; liminalnost; meantime; medčasje; Negotovost; pandemics; Pandemije; social exclusion; uncertainty